Gottron’s papules of dermatomyositis/Flat warts. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2007)
Gottron's papules of dermatomyositis, when affecting exclusively or mainly the dorsal aspect of the hands, should be differentiated from flat warts, which need a different treatment. Even more difficult is the differential diagnosis, when flat warts of the dorsal aspect of the hands affect a patient with dermatomyositis.